Excited-state proton transfer relieves antiaromaticity in molecules - Wu, Chia-Hua (Proc Natl Acad Sci U S A, 2019)
Baird’s rule explains why and when excited-state proton transfer (ESPT) reactions happen in organic compounds. Bifunctional compounds that are [4n + 2] π-aromatic in the ground state, become [4n + 2] π-antiaromatic in the first (1)ππ* states, and proton transfer (either inter- or intramolecularly) helps relieve excited-state antiaromaticity. Computed nucleus-independent chemical shifts (NICS) for several ESPT examples (including excited-state intramolecular proton transfers (ESIPT), biprotonic transfers, dynamic catalyzed transfers, and proton relay transfers) document the important role of excited-state antiaromaticity. o-Salicylic acid undergoes ESPT only in the “antiaromatic” S(1) ((1)ππ*) state, but not in the “aromatic” S(2) ((1)ππ*) state. Stokes’ shifts of structurally related compounds [e.g., derivatives of 2-(2-hydroxyphenyl)benzoxazole and hydrogen-bonded complexes of 2-aminopyridine with protic substrates] vary depending on the antiaromaticity of the photoinduced tautomers. Remarkably, Baird’s rule predicts the effect of light on hydrogen bond strengths; hydrogen bonds that enhance (and reduce) excited-state antiaromaticity in compounds become weakened (and strengthened) upon photoexcitation.